A Review on CSP and CPVT Technologies: Energy, Economic Analysis and Recycling towards Circular Economy. (1st March 2023) - Wong, Weng Pin; Walvekar, Rashmi; Vaka, Mahesh; Khalid, Mohammad; Mubarak, Nabisab Mujawar
Abstract : Recently, there has been a shift towards renewable energy sources for electricity generation due to rapidly depleting non-renewable energy sources. Solar energy is generally the most promising renewable energy source to be harvested by concentrated solar power (CSP) and solar photovoltaic (PV) technologies. CSP technology can be further classified into a few categories, such as parabolic trough collector (PTC), solar power tower (SPT), linear Fresnel reflector (LFR), and solar parabolic dish (SPD). In contrast, solar PV can be further developed into concentrated photovoltaic (CPV) and concentrated photovoltaic thermal (CPVT) systems. The modifications (e.g. optical and thermal modifications) done on PTC and parabolic trough based CPVT systems on enhancing system performance were also discussed. Next, the economic analyses conducted for both systems were also discussed to compare the economic feasibility of the technologies employed in different countries. The appropriate recycling and CE approaches applied for PTC and PV technologies were also reviewed and classified based on the key material elements within this industry. Overall, this paper compared PTC and parabolic trough-based CPVT systems from the technical, economic, and environmental aspects to provide insight for the solar energy harvesting field researchers.